2014
DOI: 10.1007/s13318-014-0191-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sunitinib on the plasma exposure of intravenous paracetamol and its major metabolite: paracetamol glucuronide

Abstract: The study aimed to examine the effect of sunitinib on the plasma exposure of intravenous paracetamol and its major metabolite, paracetamol glucuronide. Both drugs share metabolic pathways in the liver, and the drug interactions between sunitinib and paracetamol administered in higher doses were reported. These interactions resulted in hepatotoxicity. The adult New Zealand male rabbits were divided into three groups (6 animals each): rabbits receiving sunitinib and paracetamol (SUN + PC), rabbits receiving suni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The study on the sunitinib and paracetamol interaction in rabbits proved that concomitant administration of the drugs (25 mg p.o ., 35 mg/kg b.w. i.v., respectively), contributed to lower exposure and faster clearance of paracetamol [ 21 ]. Furthermore, the same authors observed that another TKI – erlotinib, modified the metabolism of paracetamol, reducing its glucuronidation and intensifying its sulphation.…”
Section: Discussionmentioning
confidence: 99%
“…The study on the sunitinib and paracetamol interaction in rabbits proved that concomitant administration of the drugs (25 mg p.o ., 35 mg/kg b.w. i.v., respectively), contributed to lower exposure and faster clearance of paracetamol [ 21 ]. Furthermore, the same authors observed that another TKI – erlotinib, modified the metabolism of paracetamol, reducing its glucuronidation and intensifying its sulphation.…”
Section: Discussionmentioning
confidence: 99%
“…In the I S+PA group we also observed increased C max and AUC 0-∞ of paracetamol sulphate by 2.1-and 2.7-fold, respectively with a simultaneous increase in paracetamol sulphate/paracetamol ratio for C max and AUC 0-∞ (p = 0.0003 and p = 0.0003, respectively). Karbownik et al [36][37][38] conducted an in vivo study and proved that other TKIs, i.e. erlotinib, lapatinib and sunitinib significantly affected the PK of paracetamol.…”
Section: The Influence Of Sorafenib On the Pharmacokinetics Of Paracementioning
confidence: 99%
“… The green dots are the data adopted from the work of [ 61 ]. CYP protein mediated hepatic clearance was parameterised with Vmax = 40 μmol/L/min, Km = 10 μmol/L and considering a liver concentration of the enzyme of 1μmol/L.…”
Section: Supporting Informationmentioning
confidence: 99%